Pemasaran Ayam Broiler di Kabupaten Lombok Utara terhadap nilai Tambah - Ashari, Ashari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Broiler chickens are superior breeds of chicken produced by crosses from chicken nations that have high productivity, especially in chicken meat production. Until now broiler chickens have been known to the Indonesian people with various advantages. Broiler chicken farms have a relatively short maintenance time and harvest time which is considered fast among other meat-producing livestock commodities. This indicates that the availability of broiler chicken meat supply tends to be continuous. In addition, many consumers tend to prioritize the consumption of broiler meat to fulfill their animal protein needs, so that many business people are interested in pursuing broiler farming because of their rapid capital turnover. In value added analysis there are three supporting components, namely: 1) Conversion factor, showing the amount of output produced from one unit of input, 2) Factor coefficient of labor, indicating the amount of labor needed to process one input unit, and 3) Product value , shows the output value per input unit. The average output value of the sale of broiler chickens obtained by large cutter traders is Rp. 28,500 per head, for small cutter traders Rp. 33,650 per head while at retailers Rp. 33,650 per output value is obtained. from the multiplication of the output price variable (selling price) with the conversion factor. The price of output for large cutter traders is smaller because the sale of products to small cutter traders and retailers. The added value of broiler chicken marketing obtained by large cutter traders is Rp.7,909.23 per head (27.75%) and small cutter traders get Rp.10,195.45 (30.30%) per head, while retailers get value added Rp.3,940.52 (11.71%) per head. Overall, small cutter traders get greater profits than large cutter traders and retailers, this is because small cutter traders buy live chicken raw materials to large cutter traders and sell them in the form of carcasses and non carcasses to end consumers. The average marketing margin obtained by large cutter traders is Rp 10,000 per head, while for small cutter traders Rp 10,500 per head, and retailers Rp.5,150 per head.